Burn first aid knowledge in Germany and the influences of social-economic factors. Issue 6 (September 2020) - Schiefer, Jennifer Lynn; Schuller, Hannelore; Fuchs, Paul Christian; Grigutsch, Daniel; Klein, Matthias; Ribitsch, Benedikt; Schulz, Alexandra
Highlights: Burn first aid knowledge in Germany needs improvement. We demonstrated the lack of knowledge based on the case scenarios from Wallace et al used in 2013 in Australia. More than 40% of all questioned people had taken part in a first aid training, which unfortunately did not lead to more correct answers. Abstract: Background: Optimal management of burns always starts with the first aid. Results of numerous studies carried out in different countries indicated in general a low awareness of first aid of burns irrespective of whether the income of the country was high, middle or low. The aim of the study was to investigate the knowledge in burn first aid in Germany and compare it to an Australian study from 2013. Methods: From January 2016 until August 2017 patients, visitors and medical personnel in the emergency room of two large hospitals in Southern and the Western part of Germany were asked to take part in a paper based multiple-choice survey. Results: Altogether 1229 people took part in the questionnaire, 588 from Bavaria and 641 from North Rhine-Westphalia; 45, 2% males and 54.8% females. Their age ranged from 19 to 52 with a mean of 37.2 years. Hereby participants that had taken part in first aid training and people working in health care had significant more correct answers. Overall, only approximately a third of the given answers were correct. Conclusion: Our study suggests that there is room for improvement since only a minority of the German population is familiar with first aid principles dealing with burns. Although more than 40% had taken part in a first aid training, the questioned people gave less correct answers than the Australians in 2013.